2022
DOI: 10.3389/fnhum.2021.789467
|View full text |Cite
|
Sign up to set email alerts
|

Rhythm and Music-Based Interventions in Motor Rehabilitation: Current Evidence and Future Perspectives

Abstract: Research in basic and clinical neuroscience of music conducted over the past decades has begun to uncover music’s high potential as a tool for rehabilitation. Advances in our understanding of how music engages parallel brain networks underpinning sensory and motor processes, arousal, reward, and affective regulation, have laid a sound neuroscientific foundation for the development of theory-driven music interventions that have been systematically tested in clinical settings. Of particular significance in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 243 publications
(388 reference statements)
4
43
0
Order By: Relevance
“…Nowadays, music intervention has a similar purpose when compared to physical activity in patients with AD, but music intervention may use totally different techniques to achieve these goals. Music intervention utilizes methods such as rhythmic auditory stimulation (RAS), therapeutic instrumental music performance, and musical neglect training to patients’ movement ( Wittwer et al, 2019 ; Braun Janzen et al, 2021 ). Studies about combined physical activity and music intervention are very limited, but it has proven important for patients with AD.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, music intervention has a similar purpose when compared to physical activity in patients with AD, but music intervention may use totally different techniques to achieve these goals. Music intervention utilizes methods such as rhythmic auditory stimulation (RAS), therapeutic instrumental music performance, and musical neglect training to patients’ movement ( Wittwer et al, 2019 ; Braun Janzen et al, 2021 ). Studies about combined physical activity and music intervention are very limited, but it has proven important for patients with AD.…”
Section: Resultsmentioning
confidence: 99%
“…In a neurorehabilitation setting, Street et al (2019) found indications that the auditory-motor pathway can be potentially fortified when the external auditory cues are internalized and patients are able to synchronize their movements independently. Other studies using Rhythmic Auditory Stimulation, which is also based on auditory-motor synchronization, have demonstrated its high success in gait training for various neuropathological gait disorders ( Thaut and Abiru, 2010 ; Braun Janzen et al, 2022 ). Studies have also supported the efficacy of music therapy on mood, depressive syndromes, and the quality of life of neurological patients ( Raglio, 2015 ).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…The use of music therapy-based auditory stimulations (MT) to achieve therapeutic goals has emerged as a promising intervention for individuals with TBI and SCI [ 10 ]. MT has been shown to influence various aspects of physical and cognitive functioning [ 11 ], including gait, in individuals with TBI and SCI [ 12 , 13 , 14 ]. Studies have suggested several methods by which MT can facilitate the spatial and temporal aspects of gait (i.e., speed, cadence, stride length etc.).…”
Section: Introductionmentioning
confidence: 99%